How Patients Perceive Their Doctors' Communication: Implications for Patient Willingness to Communicate. (December 2015) - Baker, Susan C.; Watson, Bernadette M.
By emphasizing the value of health professionals' communication skills in creating positive health care experiences, researchers have tended to study health communication as an interpersonal encounter. Interactions in the health context, though, are inherently intergroup. Using the language and social psychology approach, this study emphasizes those intergroup features of health communication. We used mixed methods and applied communication accommodation theory and the willingness to communicate construct to the health context. Participants in Canada and Australia ( N = 371) were asked about their perceptions of their health consultations. Multiple regression analyses revealed that health communication competence was the best predictor of patient willingness to communicate. Differences between patients' accounts of positive and negative health care experiences were clearly differentiated by their perceptions of the health professionals' communication strategies. The potential effects of these strategies on patient participation are discussed.